Security of retail payments: The new strategic objective - Joanna Stavins (Federal Reserve Bank of Boston, 2013)
The Federal Reserve Financial Services Strategic Plan for 2012 - 2016 specifies five main policy goals for the next few years. The second of its goals is to "Maintain public confidence in the end-to-end safety and security of clearing and settlement systems." Indeed, in each annual Survey of Consumer Payment Choice (SCPC), respondents consistently rank security as the most important characteristic of payment methods. However, in regressions of consumer payment use, security is not as significant as other payment attributes, such as cost, convenience, or record keeping. We analyze that puzzle by looking closely at how consumers' assessments of payment method security relate to their actual payment behavior, including testing whether consumers are more likely to use payment methods they consider more secure. Econometric results show that concerns about security create an obstacle to the adoption of some of the bank account-based payments - debit cards, online banking bill pay, and bank account number payments - but once adopted, there is no significant effect of security rating on the use of those payment instruments. The reverse is found for more established payment methods - cash, checks, and credit cards: consumers' perception of security does not influence adoption, but it does affect their actual payment use. Policy simulation results show that security improvements applied to individual payment instruments would increase the adoption of some payments, but once those payment instruments were adopted, security improvements would have only a small effect on the use of those payments.
Keywords: D14; D12; G28; 330